2014
DOI: 10.1371/journal.pone.0092371
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood TIM-3 Positive NK and CD8+ T Cells throughout Pregnancy: TIM-3/Galectin-9 Interaction and Its Possible Role during Pregnancy

Abstract: ProblemThe T-cell immunoglobulin and mucin domain (TIM) family is a relatively newly described group of molecules with a conserved structure and important immunological functions. Identification of Galectin-9 as a ligand for TIM-3 has established the Galectin-9/TIM-3 pathway as an important negative regulator of Th1 immunity and tolerance induction. Data about the TIM-3/Gal-9 pathway in the pathogenesis of human diseases is emerging, but their possible role during human pregnancy is not precisely known. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 30 publications
1
72
0
5
Order By: Relevance
“…T-cell immunoglobulin and mucin-domain containing-3 (Tim3) is the most well characterized binding partner of galectin-9, and their interaction was shown to negatively regulate Th1 type responses through apoptosis of activated CD4+ cells (13, 14). Remarkably, galectin-9/Tim3 regulation at the feto-maternal interface seems to be critical for the development and maintenance of healthy pregnancies (15, 16). Many similarities exist between tumor and trophoblastic development and regulation in promoting immune tolerance (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…T-cell immunoglobulin and mucin-domain containing-3 (Tim3) is the most well characterized binding partner of galectin-9, and their interaction was shown to negatively regulate Th1 type responses through apoptosis of activated CD4+ cells (13, 14). Remarkably, galectin-9/Tim3 regulation at the feto-maternal interface seems to be critical for the development and maintenance of healthy pregnancies (15, 16). Many similarities exist between tumor and trophoblastic development and regulation in promoting immune tolerance (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…14 Functional studies of Gal-9 with Th1, Th2, Th17, Treg, and NK cells have been carried out extensively. 15,16 However, fewer evidences with THP-1/differentiated THP-1 such as myeloid lineage immune cells compared to lymphoid lineage immune cells have been shown. Many recent studies have shown that TIM-3 is expressed in myeloid lineage immune cells, notably antigen-presenting cells (APSs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have demonstrated that T cell immunoglobulin and mucin domain 3 (Tim-3) is closely associated with dysregulation of innate immune cells, including macrophages/monocytes (Yang et al, 2013), dendritic cells (Chiba et al, 2012), and NK cells (Gleason et al, 2012). Abnormal expression of Tim-3 on these innate immune cells was found to be involved in the progression of many clinical diseases (Wu et al, 2012;Anderson et al, 2012;da Silva et al, 2014;Meggyes et al, 2014). However, it was not reported the relationship between Tim-3 expression on NK cells and NKT cells and lung cancer.…”
Section: Introductionmentioning
confidence: 99%